2016
DOI: 10.1071/sr15336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of grain yields and N2O emissions on Oxisol and Vertisol soils in response to fertiliser N applied as urea or urea coated with the nitrification inhibitor 3,4-dimethylpyrazole phosphate

Abstract: Abstract. The potential for elevated nitrous oxide (N 2 O) losses is high in subtropical cereal cropping systems in northeast Australia, where the fertiliser nitrogen (N) input is one single application at or before planting. The use of urea coated with the nitrification inhibitor 3,4-dimethylpyrazole phosphate (DMPP) has been reported to substantially decrease N 2 O emissions and increase crop yields in humid, high-intensity rainfall environments. However, it is still uncertain whether this product is similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 40 publications
(48 reference statements)
2
1
0
Order By: Relevance
“…3 ). This is in agreement with the reductive effect of NI reported from cereal cropping systems under similar soil and climatic conditions, where a N 2 O emission reduction ranging from 30–80% has been reported 24 25 26 . It is also within the range of reduction reported for intensively managed vegetable systems 5 15 16 23 27 28 .…”
Section: Discussionsupporting
confidence: 92%
“…3 ). This is in agreement with the reductive effect of NI reported from cereal cropping systems under similar soil and climatic conditions, where a N 2 O emission reduction ranging from 30–80% has been reported 24 25 26 . It is also within the range of reduction reported for intensively managed vegetable systems 5 15 16 23 27 28 .…”
Section: Discussionsupporting
confidence: 92%
“…3). This is in good agreement with results from studies in other sub-tropical cereal systems in Australia (De Antoni Migliorati et al 2014;Jamali et al 2015;Schwenke et al 2015;De Antoni Migliorati et al 2016) where emission pulses were generally observed after heavy rainfall or irrigation. These emission pulses are typically triggered by the combination of high soil moisture, high availability of NO 3 --N following fertilisation and high soil temperatures.…”
Section: Temporal Variability Of N 2 O Emissionssupporting
confidence: 82%
“…This unit is based on the original system as described in Breuer et al. (2000) and has been used extensively in Australia (Barton et al., 2008; Barton, Butterbach‐Bahl, Kiese, & Murphy, 2010; De Antoni Migliorati et al., 2015, 2016; De Rosa et al., 2016, 2018; Kiese & Butterbach‐Bahl, 2002; Mumford, Rowlings, Scheer, De Rosa, & Grace, 2019; Rowlings et al., 2012, 2013; 2015; Scheer et al., 2011, 2012, 2014, 2016; Schwenke et al., 2015, 2016; Schwenke & Haigh, 2016; van Delden, Rowlings, Scheer, & Grace, 2016; van Delden, Rowlings, Scheer, De Rosa, & Grace, 2018; Wang, Dalal, Reeves, Butterbach‐Bahl, & Kiese, 2011; Wang et al., 2016) as a key component of the Australian National Agricultural Nitrous Oxide Research Program (NANORP) (Grace, 2016; Grace et al., 2010). The modified system, which we call the “Queensland” system, is now produced by Queensland University of Technology (Brisbane, Australia) in collaboration with Karlsruhe Institute of Technology (Garmisch, Germany) (Figure 2).…”
Section: Factors Influencing Sample Acquisitionmentioning
confidence: 99%